Формирование композиционных покрытий никель – бор – азот - Кузей, А.М.; Таран, И.И. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
The methods of X-ray analysis and electron microscopy have been used to study the structure of nitrogen-ion implanted electrochemical Ni–B coatings with the boron concentration of 8,14 and 20 at %. The implantation is shown to increase coating microhardness from 5,1-5,9 GPa to 10,8-11,7 GPa. The hardness increase of coatings is attributed to decrease of nickel boride particle size and formation of γ-BN.